Chemerin Suppresses Breast Cancer Growth by Recruiting Immune Effector Cells Into the Tumor Microenvironment - Pachynski, Russell K.; Wang, Ping; Salazar, Nicole; Zheng, Yayue; Nease, Leona; Rosalez, Jesse; Leong, Weng-In; Virdi, Gurpal; Rennier, Keith; Shin, Woo Jae; Nguyen, Viet; Butcher, Eugene C.; et al. (Frontiers in Immunology, 2019)
Infiltration of immune cells into the tumor microenvironment (TME) can regulate growth and survival of neoplastic cells, impacting tumorigenesis and tumor progression. Correlations between the number of effector immune cells present in a tumor and clinical outcomes in many human tumors, including breast, have been widely described. Current immunotherapies utilizing checkpoint inhibitors or costimulatory molecule agonists aim to activate effector immune cells. However, tumors often lack adequate effector cell numbers within the TME, resulting in suboptimal responses to these agents. Chemerin (RARRES2) is a leukocyte chemoattractant widely expressed in many tissues and is known to recruit innate leukocytes. CMKLR1 is a chemotactic cellular receptor for chemerin and is expressed on subsets of dendritic cells, NK cells, and macrophages. We have previously shown that chemerin acts as a tumor suppressive cytokine in mouse melanoma models by recruiting innate immune defenses into the TME. Chemerin/RARRES2 is downregulated in many tumors, including breast, compared to normal tissue counterparts. Here, using a syngeneic orthotopic EMT6 breast carcinoma model, we show that forced overexpression of chemerin by tumor cells results in significant recruitment of NK cells and T cells within the TME. While chemerin secretion by EMT6 cells did not alter their phenotypic behavior in vitro, it did significantly suppress tumor growth in vivo. To define the cellular effectors required for this anti-tumor phenotype, we depleted NK cells or CD8+ T cells and found that either cell type is required for chemerin-dependent suppression of EMT6 tumor growth. Finally, we show significantly reduced levels of RARRES2 mRNA in human breast cancer samples compared to matched normal tissues. Thus, for the first time we have shown that increasing chemerin expression within the breast carcinoma TME can suppress growth by recruitment of NK and T cells, thereby supporting this approach as a promising immunotherapeutic strategy.